Pulsatile Scalp Swelling - Das, Susanta Kumar (Springer India, 2012)
Metastasis from follicular carcinoma is usually blood-borne. Here, we present a case of skull metastasis with intracranial extension presenting as a pulsatile scalp swelling from the follicular thyroid carcinoma.